2017
DOI: 10.7324/japs.2017.70931
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior and Pharmaceutical Applications of Bacterial Exopolysaccharides

Abstract: Over the last few decades, numerous bacterial exopolysaccharides have been extensively studied for their composition, structure, biosynthesis and functional properties, owing to their unique properties over traditional plant-derived gums and synthetic polysaccharides. They have been employed in food processing industries as rheology modifiers, gelling agents, in oil drilling and cement industries. But their full-fledged commercialization is yet to be achieved and their scope and possibilities in pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Microbial polysaccharides are extracellular polymeric substances either soluble or insoluble that are synthesized by bacteria, yeast, algae, fungi etc. are considered to be value added substances and exploited for different purposes [1,2]. EPS are metabolic by-products of microorganisms [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial polysaccharides are extracellular polymeric substances either soluble or insoluble that are synthesized by bacteria, yeast, algae, fungi etc. are considered to be value added substances and exploited for different purposes [1,2]. EPS are metabolic by-products of microorganisms [3].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27]. EPS has strong water binding ability, water retention capacity, immense swelling and gelation potential [2]. EPS like xanthan, sphingan, alginate, cellulose promotes biofilm formation on the bacterial cell surfaces as a protecting barrier [28].…”
Section: Introductionmentioning
confidence: 99%
“…Levan solutions also exhibit an atypical behaviour when compared to other polysaccharides, in which gel formation is not observed ( 129 , 130 ). However, Jakob et al ( 131 ), when establishing the structure/function relationship of isolated AAB levans, suggested that in a solution, increasing their molecular mass reinforces intramolecular interactions to achieve a more compact structure characteristic of a ’microgel’ with hydrocolloid properties.…”
Section: Exopolysaccharides Produced By Aabmentioning
confidence: 99%
“…6 In agriculture, EPSs have been used to improve the flow of pesticides and uniformly disperse solid components in formulations; the improved rheology of the formulation also ensures surface cling. 7 Exopolysaccharides are also used as gelling agents for culture media, paints and ink, and detergents.…”
Section: Introduction Exopolysaccharidesmentioning
confidence: 99%